Exploring stigma as a barrier to cancer service engagement with breast cancer survivors in Kampala, Uganda. Issue 10 (21st August 2016) - Meacham, Elizabeth; Orem, Jackson; Nakigudde, Gertrude; Zujewski, Jo Anne; Rao, Deepa
Abstract: Objective: To understand the role of stigma in the delay of cancer service engagement by women with breast cancer in Kampala, Uganda. Background: Women in Sub‐Saharan African countries are twice as likely to die from cancer as women in high‐income countries, which is largely attributable to late diagnosis. While breast cancer‐related stigma has been identified in Sub‐Saharan Africa, limited research focuses on how stigma impacts the behavior of breast cancer patients in Uganda. Methods: This qualitative study used a grounded theory approach to examine illness narratives from 20 breast cancer survivors in Uganda, gathered through semistructured interviews. Results: Thematic analysis showed that perceived and internalized stigma associated with breast cancer influenced care engagement throughout illness, delaying engagement and inhibiting treatment completion. Women identified key factors for overcoming stigma including acceptance of diagnosis, social support, and understanding of breast cancer. Conclusion: The growing burden of mortality associated with breast cancer in Uganda can be mitigated by improving early detection and treatment engagement through interventions which account for key psychosocial barriers such as stigma.